Resilience of Amazon forests emerges from plant trait diversity - Sakschewski, Boris; von Bloh, Werner; Boit, Alice; Poorter, Lourens; Peña-Claros, Marielos; Heinke, Jens; Joshi, Jasmin; Thonicke, Kirsten (Nature climate change, 2016)
Application of a terrestrial biogeochemical model that simulates diverse forest communities suggests that plant trait diversity may enable the Amazon rainforest to adjust to new climate conditions via a process of ecological sorting. Climate change threatens ecosystems worldwide, yet their potential future resilience remains largely unquantified 1 . In recent years many studies have shown that biodiversity, and in particular functional diversity, can enhance ecosystem resilience by providing a higher response diversity 2 , 3 , 4 , 5 . So far these insights have been mostly neglected in large-scale projections of ecosystem responses to climate change 6 . Here we show that plant trait diversity, as a key component of functional diversity, can have a strikingly positive effect on the Amazon forests’ biomass under future climate change. Using a terrestrial biogeochemical model that simulates diverse forest communities on the basis of individual tree growth 7 , we show that plant trait diversity may enable the Amazon forests to adjust to new climate conditions via a process of ecological sorting, protecting the Amazon’s carbon sink function. Therefore, plant trait diversity, and biodiversity in general, should be considered in large-scale ecosystem projections and be included as an integral part of climate change research and policy.